2019
DOI: 10.1186/s12889-019-7505-7
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of goiter among children in Ethiopia and associated factors: a systematic review and meta-analysis

Abstract: Background: The distribution of goiter among children and its risk factors are not well investigated in Ethiopia. Therefore, this systematic review and meta-analysis was designed to determine the pooled prevalence of goiter and its associated factors among children in Ethiopia. Methods: Electronic web-based searches of PubMed, Google Scholar, EMBASE, and the World Health Organization's Hinari portal (which includes the SCOPUS, African Index Medicus, and African Journals Online databases) were conducted to find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 50 publications
1
8
0
Order By: Relevance
“…The reduced prevalence of iodine deficiency in the study area is promising. However, iodine deficiency was still a public health problem in some parts of the country [26][27][28]. A study conducted in the Robe district in 2015 showed that 57% of the participants had low UIC and the median UIC was 78 μg/L [29].…”
Section: Discussionmentioning
confidence: 99%
“…The reduced prevalence of iodine deficiency in the study area is promising. However, iodine deficiency was still a public health problem in some parts of the country [26][27][28]. A study conducted in the Robe district in 2015 showed that 57% of the participants had low UIC and the median UIC was 78 μg/L [29].…”
Section: Discussionmentioning
confidence: 99%
“…IDDs affect people of all ages, but young children, women of reproductive age, pregnant women, and lactating women are the most vulnerable [4]. IDDs remain a public health concern [6]. Previous studies in South Asia [7][8][9][10] and Sub-Saharan Africa [7,[11][12][13][14] have found that iodized salt is in short supply at the household (HH) level.…”
Section: Introductionmentioning
confidence: 99%
“…Our finding is slightly higher than the previous review which reported 40.5%. 24 The difference could be related to the difference in the study population, the previous review included children and adolescents while ours focus on school-age children only. According to the world health organization guideline, a total goiter rate of 30% or more among school-age (6–12 years) children signals the existence of severe public health problems.…”
Section: Discussionmentioning
confidence: 89%
“… 23 A recent systematic review in Ethiopia reported a 40.5% prevalence of goiter among people aged 6–18 years old. 24 This systematic review and meta-analysis aimed to estimate the pooled prevalence of goiter among school-aged children (6-12 years) in Ethiopia. The prevalence of goiter among school children is used as a key indicator of population-level of iodine deficiency both due to their physiologic vulnerability and ease of accessibility through schools.…”
Section: Introductionmentioning
confidence: 99%